From Tradition to Innovation: Mind Map Generation in Higher Education - Mitra, Aditya Rama; Samosir, Feliks Victor Parningotan; Hudi, Robertus; Tarigan, Riswan Effendi (ULTIMA InfoSys, 2023)
In higher education, effectively delivering complex topics to students with diverse learning preferences remains a pressing challenge. This comprehensive survey delves into the utilization of mind maps as an innovative instructional tool to navigate this challenge. From 2003 to 2022, we review the implementation of mind maps in higher education, highlighting aspects such as the year of the paper, the techniques employed for mind mapping, target audiences, objectives, and outcomes. Mind maps, centralized and radial visual techniques, have been recognized for their capacity to enhance memory retention, comprehension, and active student engagement. We identify two primary scenarios: Learner-Driven and Lecturer-Driven Development. While students employ mind maps for revision and understanding, lecturers utilize them as visual aids to structure content and elucidate intricate relationships. The paper underscores the need for inclusivity, accommodating varied learning styles, and integrating mind maps into a broader educational toolkit. Through this study, we uncover research gaps and propose future avenues to further amplify the potential of mind maps in academia.